Getúlio Vargas, do homem ao mito político: a desconstrução de uma imagem (1930-1945) - Santana, Samantha Perez de (2010)
This paper aims to analyze and deconstruct the image created by Getúlio Vargas through photographic production from 1930 to 1945. The images deal with several faces assigned to Vargas compose the political imaginary of the period, pointing to the importance of understanding how the use of these images was guided and by intentions, interests, conflicts and political projects. The set of documents used in this study is found in iconographic collection of CPDOC (Brazilian Contemporaneous History Research Center). The images research showed to different approaches about the social production of photography and also how the cultural filters that surround it - the photographer, the represented people, the setting and the theme assigned - can influence on the picture, building and educate the eye